2006
DOI: 10.4049/jimmunol.177.11.8266
|View full text |Cite
|
Sign up to set email alerts
|

IL-22-Mediated Tumor Growth Reduction Correlates with Inhibition of ERK1/2 and AKT Phosphorylation and Induction of Cell Cycle Arrest in the G2-M Phase

Abstract: IL-22 is a recently discovered cytokine of the IL-10 family that binds to a class II cytokine receptor composed of IL-22R1 and IL-10R2c and influences a variety of immune reactions. As IL-22 has also been shown to modulate cell cycle and proliferation mediators such as ERK1/2 and JNK, we studied the role of IL-22 in proliferation, apoptosis, and cell cycle regulation in EMT6 murine breast cancer cells in vitro and in vivo. In this study, we report that murine breast cancer cells express functional IL-22R as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 44 publications
7
44
0
Order By: Relevance
“…Previous reports indicated that IL-22 induces the proliferation of several cell lines including keratinocytes, SW480, and IL-22R1-transfected BaF3 and inhibits keratinocyte differentiation [9,[45][46][47]. However, IL-22 was shown to reduce EMT6 cell proliferation in both in vitro and in vivo [44]. Together, our data and others' further support the notion that IL-22 exerts specific effects in different cell types.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous reports indicated that IL-22 induces the proliferation of several cell lines including keratinocytes, SW480, and IL-22R1-transfected BaF3 and inhibits keratinocyte differentiation [9,[45][46][47]. However, IL-22 was shown to reduce EMT6 cell proliferation in both in vitro and in vivo [44]. Together, our data and others' further support the notion that IL-22 exerts specific effects in different cell types.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed activation of Erk1/2 in IL-22-stimulated human colorectal cancer SW480 cells and IL-22-induced activation of the three major MAPK pathways (Erk1/2, Jnk, and p38) in IL-22R1-expressing HEK293 cells [9]. On the other hand, it inhibited phosphorylation of Erk1/2 in EMT6 murine breast cancer cells [44]. In this study, we observed that IL-22 activated p38 MAPK pathway, inhibited phosphorylation of Erk/MAPK, but did not affect the Jnk phosphorylation in naïve PC12 cells.…”
Section: Discussionmentioning
confidence: 51%
“…In keeping with the previous findings of IL-22-mediated activation of STAT3 in a number of epithelial cell types, 22,30,31 we found that STAT3 activation can be enhanced by IL-22 in ALK þ ALCL cells. The importance of IL-22 in contributing to STAT3 activation in these cells is further supported by our findings that blockade of IL-22 signaling using siRNA, IL-22BP or an IL-22-neutralizing antibody substantially decreased STAT3 activation.…”
Section: Discussionsupporting
confidence: 77%
“…28,29 IL-22R1 is characteristically absent in benign immune cells including lymphocytes [16][17][18] in various epithelial cell lines, IL-22 has been shown to promote cell proliferation and activate a number of signaling pathways including those of STAT3, MAPK and AKT. 22,30 It is currently believed that the physiological function of IL-22 is related to the maintenance of innate immunity. 23 One of the significant findings of this study is that of aberrant expression of IL-22R1 in ALK þ ALCL, a type of mature T-cell neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Although the growth of IL-22-transfected colon 26 cells was not different from that of control cells in vitro, survival of inoculated mice was significantly prolonged compared with control mice, suggesting that IL-22 might play a protective role in the mice with colon carcinoma (15). In contrast, Weber et al (16) reported that IL-22 reduced EMT6 murine breast tumor growth by inhibiting ERK1/2 and AKT phosphorylation. On the other hand, in an in vitro study using HepG2 human hepatocellular carcinoma cells, it was noted that IL-22 transfection promoted cell growth and survival by activation of STAT3 and induction of antiapoptotic and mitogenic proteins (10).…”
Section: Discussionmentioning
confidence: 86%